A rare case of Wilkie`s syndrome with infantile hypertrophic pyloric stenosis - Stamov, Petar; Stamova, Sylvia (Medicine and Pharmacy Reports, 2024)
Wilkie’s syndrome is a rare clinical disorder characterized by partial or complete obstruction of the duodenum. Infantile hypertrophic pyloric stenosis (IHPS) is defined as hyperplasia of the smooth muscle fibers of the pylorus, which is considered responsible for narrowing the pyloric canal and eventually obstructing the gastric outlet. This paper presents a case of a 3-month-old boy who had been vomiting after feeding for one month. The main symptoms, postprandial vomiting, dehydration, alkalosis, and weight reduction, point to the IHPS disease. Imaging studies also confirmed the diagnosis. During the surgical treatment, a concomitant condition known as Wilkie’s syndrome was also evidenced. The team performed a complex surgical treatment of a patient diagnosed with both Wilkie’s syndrome and IHPS within one single surgical operation. Surgical treatment with pyloromyotomy and duodenal-duodenal anastomosis within one operation is an optimal option for one-stage treatment of patients with IHPS and Wilkie’s syndrome.